Analysis Of Nursing Care in Post Laparotomy TAH-BSO Patient Using Finger Grip Relaxation Therapy - Septiyono, Eka Afdi; Seniwati, Yuliana Eka Galuh Seniwati; Sulistyorini, Lantin; Kisnawati, Eni (Al-Hijrah Indonesia, 2024)
Handling of chocolate cysts can be done by laparotomy surgery. The surgical procedure has an effect or problem that often arises, namely acute pain in the area of the former operation. One of the therapies that can be given to patient with post-laparotomy surgery is finger grip relaxation techniques. This technique is considered capable of reducing the intensity of pain in postoperative patient, in addition to that finger-held relaxation therapy is an effective, comfortable, easy to use, and inexpensive therapy so that all patient can obtain and perform this therapy.This work aims to determine the effectiveness of applying finger-hold relaxation techniques to patient with post-laparotomy surgery for indications of chocolate cysts.The method used in this research is a case study on patient in the Dahlia room, dr. Soebandi General Hospital with a diagnosis of acute pain.The results after being given the intervention of finger-held relaxation techniques for 3 consecutive days with 2 sessions per day for 15 minutes with 3-minute intervals changing the fingers held were a decrease in pain intensity from sharp pain that was felt continuously with a scale of 6 NRS to a recurring, intermittent pain with a pain scale of 3 NRS.